Late Lung Metastasis of a Primary Eccrine Sweat Gland Carcinoma 10 Years after Initial Surgical Treatment: The First Clinical Documentation. (28th April 2013) - Falkenstern-Ge, R. F.; Bode-Erdmann, S.; Ott, G.; Wohlleber, M.; Kohlhäufl, M.
Abstract : Background . Sweat gland carcinoma is a rare malignancy with a high metastatic potential seen more commonly in elderly patients. The scalp is the most common site of occurrence and it usually spreads to regional lymph nodes. Liver, lungs, and bones are the most common sites of distant metastasis. Late lung metastasis of sweat gland adenocarcinoma after a time span of 5 years is extremely rare. Aim . We report a patient with late lung metastasis of a primary sweat gland carcinoma 10 years after initial surgical resection. Conclusion . Sweat gland carcinomas are rare cancers with a poor prognosis. Surgery in the form of wide local excision and lymph node dissection is the mainstay of treatment. Late pulmonary metastases with a latency of 10 years have never been reported in the literature. This is the first clinical documentation of late lung metastasis from sweat gland carcinoma with a latency period of 10 years.